Community-Acquired Pneumonia and Outcome: The Importance of Genetics - Wood, Kelly A.; Marik, Paul E. (Current Respiratory Medicine Reviews, 2005)
Community-acquired pneumonia (CAP) is a major health concern and the subject of extensive research. In the past, efforts have been focused on addressing antibiotic resistance patterns, instituting preventive measures, and the development of prediction tools. Despite these efforts, improvement in outcome from CAP, particularly in the elderly, has remained inadequate. Inappropriate antibiotic therapy, potential lack of efficacy of pneumoccocal vaccine and limited use of prediction tools have led to a marked increase in attempts to explore genetic influences on CAP. There is evidence that genetics plays a role not only in acquiring CAP, but also in the ultimate outcome of this disease. Since morbidity and mortality are related to septic complications, examining the genetics of sepsis along with CAP is essential. Single nucleotide polymorphisms (SNPs) and mutations have been shown to be associated with outcomes (ex. SP-B +1580, LTA +250, and HSP70-2+1267 polymorphisms ) in CAP and infectious causes of sepsis. Unfortunately, some results have had inconsistent associations with outcome (TNF -308 and IL-10 polymorphisms); lending support to the postulation that studying larger population samples and levels of RNA expression may provide clarifying data. It is anticipated that genetic research involving CAP and its outcomes will lead to the use of genetic data in prediction and therapeutic tools.
Keywords: community-acquired pneumonia